2006
DOI: 10.1007/s10832-006-9909-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of UHV sputtering HfO2 film by plasma oxidation and low temperature annealing

Abstract: Ultra-thin (∼4.0 nm) HfO 2 films were fabricated by plasma oxidation of sputtered metallic Hf films with post low temperature annealing. Advantage of this fabrication process is that the pre-deposition of Hf metal can suppress the formation of interfacial layer between HfO 2 film and Si substrate. The as-deposited HfO 2 films were subsequently treated by rapid thermal annealing at different temperatures in N 2 to investigate the effects of thermal annealing on the physical and electrical properties of HfO 2 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Both thickness and band gap of the films decreased with increase of annealing temperature[54]. Li et al found as the highest dielectric constant of κ = 22 of HfO 2 when the film was annealed at 500 • C by plasma oxidation[67]. Yamamoto et al have analyzed the relation between leakage current density and EOT of HfO 2 films prepared by remote plasma oxidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both thickness and band gap of the films decreased with increase of annealing temperature[54]. Li et al found as the highest dielectric constant of κ = 22 of HfO 2 when the film was annealed at 500 • C by plasma oxidation[67]. Yamamoto et al have analyzed the relation between leakage current density and EOT of HfO 2 films prepared by remote plasma oxidation.…”
mentioning
confidence: 99%
“…of results of different coating methods[43,58,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. × 10 −8 A/cm 2 at 1 V EOT= 2.73 nm at 700 • C…”
mentioning
confidence: 99%